STRATEGI PEMBERDAYAAN KELEMBAGAAN PETANI DAN PASAR PERBERASAN GUNA PENINGKATAN NILAI TUKAR PETANI SERTA KETERSEDIAAN PANGAN - Raharto, Sugeng (Jurnal Sosial Ekonomi Pertanian, 2010)
The main problem often faced by the farmers, especially producers of rice farmers now is the low level of sales prices of rice especially during the peak harvest season, because of the environment and the weather is usually in conjunction with the rainy season. Another cause of low grain prices that is small scale rice farming, limited facilities and infrastructure of production and post harvest. Objectives: (1) assess the institutional role of farmers in exchange rates, (2) identify factors driving and inhibiting the dynamics of farmer institutions. The results showed, the exchange rate is influenced farmers age, education, experience, area and status of land management. Institutional conditions that encourage farmers member-owned institution, means of production are met mainly fertilizer and factors inhibiting the limited institutional capital owned by farmers.Key words: institutions, exchange rates, farmers, rice